2022
DOI: 10.24326/asphc.2022.6.7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficacy of herbal plant extracts on some phytopathogenic fungi

Abstract: Crops are subject to yield losses caused by the presence of pests whose species and population diversity are changing with climate warming. The use of agrochemicals is still the most effective method of plant protection against diseases and pests. However, the intensive use of pesticides in some EU countries makes it necessary to search for alternative methods that can be applied in plant protection for consumer and environmental safety. The aim of the study was the laboratory evaluation of the fungistatic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…The present study showed no antifungal effect against C. coccodes, and a stimulating effect on mycelial surface growth was even observed. The growth of this species was also poorly inhibited by other plant extracts, including extracts from plants with high biocidal potential [13]. Carminate et al [41] also indicated the great potential of Amaranthus viridis in controlling F. solani f. sp.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present study showed no antifungal effect against C. coccodes, and a stimulating effect on mycelial surface growth was even observed. The growth of this species was also poorly inhibited by other plant extracts, including extracts from plants with high biocidal potential [13]. Carminate et al [41] also indicated the great potential of Amaranthus viridis in controlling F. solani f. sp.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the antifungal effect of various plant extracts against F. oxysporum have been conducted by many researchers [12,17] who showed that F. oxysporum was not very sensitive to the effects of extracts from medicinal plants. Kursa et al [13] showed that 20% ethanol extracts of tansy, yarrow and horseradish, considered potent against many phytopathogens, inhibited the surface growth of F. oxysporum only at the level of 24.7-26.56%, and only in the first days of the experiment. The strong inhibitory effect of the amaranth extract was recorded against F. equiseti, mainly in relation to the extracts of A. retroflexus (TR) and A. hypochondriacus × hybrisus (PH).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations